METHODOLOGICAL APPROACHES TO THE FORMATION OF A LOGISTICS SECURITY MECHANISM FOR ENTERPRISE DEVELOPMENT - GUBAREV, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research focuses on aspects of guaranteeing stable and safe (mainly in terms of economy, finance and production) functioning and development of enterprises, organization of their logistics activities, formation and development of logistics systems, including the processes of implementing the appropriate logistics mechanism. It is emphasized that this approach is based on careful planning of various aspects and elements of the business security system. The purpose of the study is to improve the methodological and applied approaches to the formation of the logistics security mechanism of the enterprise development. It is shown that the logistics system plays an important and one of the leading roles in the sustainable and stable functioning and development of domestic enterprises. It is pointed out that an important task facing the top management of business entities is, first, strategic and tactical planning of the formation and implementation of the logistics mechanism of development; secondly, coordination of tasks and means of ensuring the development of the logistics system and strengthening the security of business development. The task of identifying and implementing opportunities and prospects for the application of innovative tools in the system of formation and implementation of the logistic mechanism of business development, oriented at the same time to strengthening the security of the sustainable development of the enterprise, has been identified. It was emphasized that the role of information and communication technologies in these processes, which open up new opportunities for the enterprise, is especially important, in particular in the areas of: quick access to information about the enterprise, as well as markets and consumers of products (services); image formation in online applications and social networks; operational identification of the main stakeholders of the enterprise; realizing the potential of Internet marketing and the absence of boundaries for communication and interaction; transfer of logistics operations online; growth in the volume of virtual trade and settlement and transport and logistics operations; combating cybercrime, etc.